KEPUASAN KERJA MEMEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL PADA PT. JAPAN TRAVEL AGENCY - Lestari, Kadek Wulan Dewi; Honor Satrya, I G. Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p08, 2023)
The role of employees is one of the keys that determine the success of the establishment of a company. Human resource management carried out by the organization can affect whether or not the goals of the organization are achieved, therefore companies must pay attention to employee job satisfaction. The purpose of this study was to analyze the influence of organizational culture on organizational commitment with job satisfaction as a mediating variable at PT. Japan Travel Agency. This study uses the method. Determination of the sample is done by sampling saturated, that is by taking the entire population of 30 respondents. Data was collected using the interview method and through questionnaires. The data analysis technique used in this research is Path Analysis and Sobel Test. The results of this study indicate that organizational culture has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on organizational commitment, and job satisfaction is a variable mediating the influence of organizational culture on organizational commitment